SAT0037 Local expression of the atypical chemokine receptor D6 in systemic sclerosis. (23rd January 2014) - Codullo, V.; Singh, M.; Baldwin, H.; Fusetti, C.; Caporali, R.; McInnes, I.; Montecucco, C.; Graham, G.
Abstract : Background: The atypical chemokine receptor D6 is an inflammatory CC-chemokine scavenger. It is involved in resolution of inflammatory responses and leukocyte trafficking from sites of injury to secondary lymphoid organs through its expression on lymphatic endothelial cells and leukocytes. Peripheral blood mononuclear cells (PBMC) from Systemic Sclerosis (SSc) patients show a marked upregulation of D6 transcript and protein, functionally relevant in buffering CC-chemokines in the circulation. Objectives: To investigate D6 expression and its potential roles in the skin of SSc patients Methods: Patients with diagnosis of SSc according to Leroy's criteria for limited cutaneous (lc), diffuse cutaneous (dc) or early disease, and healthy controls (HC), both consenting to the study according to local ethic committees, were enrolled. They underwent complete clinical evaluation, paired PBMC extraction and a skin punch biopsy on the forearm. Both cells and tissues were used for transcriptional analysis by real-time qPCR with standard curve quantification method. Transcripts were normalised to TATA-Binding Protein expression in PBMCs, to beta-actin in skin. Skin sections were double stained in immunofluorescence with anti-human D6 (R&D or Sigma) and markers of lymphatic endothelial cells (anti-human podoplanin, Sigma), or of hematopoietic derived cells (anti-CD45, Dako) and analysed by microscopy. Results: The study enrolled a total of 19 patients (mean age 57.6±15 years, 18 Females, 4 early-SSc, 12 lc-SSc and 3dc-SSc). D6 transcripts in skin were significantly upregulated in SSc patients (3443±1761 vs 1035±327 in control skin, n=9, p<0.001), with no significant differences between disease subsets and independently from D6 expression on paired PBMCs. Patients with high D6 expression showed significantly lower modified Rodnan's skin scores (mRSS) (8±7 vs 19±9 in those with no or low D6 expression) but were comparable for Valentini's disease activity scores and systemic inflammatory markers (e.g. ESR, CRP). While there was a trend for higher lymphatics/mm 2 in SSc patients, D6 protein expression was detected with no significant difference on a mean percentage of 63±15% podoplanin+ lymphatic endothelial cells in patients and HC, while D6+ leukocytes were found only on a subset of patients and HC and their presence was apparently not related to any clinical feature. D6+ leukocytes were significantly more frequent in tissues of higher CD45+ infiltration. There was a trend toward an inverse relationship between D6 expression on lymphatics and CD45+ leukocyte infiltration on the skin, being the latter higher where there was less D6 on lymphatics. Conclusions: Expression of the atypical CC-chemokine receptor D6 is upregulated in SSc skin and even in early phases of the disease. Its expression is higher in patients with lower mRSS scores indicating that it could represent an attempt to restrain local pathological activity. Inverse relationship between presence of D6 on lymphatics and leukocyte infiltration confirms this is a critical molecule in the regulation of trafficking to secondary lymphoid organs. Disclosure of Interest: None Declared